Inovasi Teknologi Dalam Meningkatkan Pelayanan Perpustakaan di Era Perpustakaan Digital - Dila Daratista; Rusdiana, Rusdiana; Ibrahim Aditya Febrian; Miftahul Rizki Br Pasaribu (Jurnal Insan Pengabdian Indonesia, 2025)
Technological innovation in libraries aims to provide library automation services. This means that the process carried out in managing a library uses information technology in which every activity in the library is integrated to facilitate and expedite the various activities or work of each library user in library services. By automating libraries, the positive impact that will occur will make the work of every library user such as librarians easier, who will experience data processing speeds that are faster than before and the accuracy of the results of searching for information needed by the library and various other activities that occur in the library. Basically, a library automation system is able to provide convenience and smoothness not only for librarians but also for all users and all parties in the library in order to achieve effectiveness and efficiency in every job. Apart from that, library automation is also very important in a library to improve the quality of services in the library and to speed up the service process in the library.